The Impact of Artificial Intelligence on The Learning Process in Higher Education - Muhammad Adenuddin Alwy; Rachmie Sari Baso (International Journal of Education and Digital Learning (IJEDL), 2024)
Artificial Intelligence (AI) is increasingly being integrated into higher education, offering significant opportunities for enhancing the learning process. This study explores the dual impact of AI on higher education, highlighting its potential to personalize learning, improve accessibility, increase teaching efficiency, and develop technical skills among students. However, alongside these benefits, AI also presents challenges, such as the risk of over-reliance on technology, exacerbating educational inequalities, reducing human interaction, and raising concerns about data privacy. Furthermore, the focus on technical skills might overshadow the importance of humanities in education. Therefore, a balanced and thoughtful implementation of AI is crucial to harness its benefits while mitigating its drawbacks, ensuring that it supports rather than undermines the fundamental goals of education.